Agriculture-nutrition linkages and child health in the presence of conflict in Nepal - Bageant, Elizabeth; Liu, Yanyan; Diao, Xinshen (International Food Policy Research Institute, 2016)
Much policy and research attention has focused on the relationship between agriculture and nutrition. We extend this analysis to the context of Nepal’s decade-long civil conflict. Understanding how conflict or similar stress mitigates the agriculture-nutrition linkage is essential to developing impactful agriculture and nutrition policy in potential conflict zones. To our knowledge, there is no prior empirical work on the link between agriculture and nutrition in the context of conflict. We find a robust relationship between milk consumption and anthropometric outcomes. We also show a positive link between milk production and milk consumption at the household level. We find significant negative relationships between conflict and milk consumption for households owning few livestock while such relationships do not exist for larger holders. We attribute these heterogeneous effects to conflict-related productivity declines and milk price increases, both of which disproportionately affect households with fewer livestock and lower milk-production capacity. Among rural households in Nepal, milk production could serve as a nutritional buffer in times of conflict or other stress, and thus, policies that promote households’ livestock production could be effective measures in improving resilience of the rural poor against shocks that negatively affect child health outcomes.